Validation of Gas-liquid Flow Maps Using Chemical Thermodynamic Simulation - Luigi Raimondi (Chemical Engineering Transactions)
The transport of liquid and vapor phases in pipes is a more complex engineering problem than that of separate phases. Two-phase transport can be found in chemical plants, production of oil and gas from wells, and reinjection of gas-oil mixtures into depleted reservoirs. Two-phase flow models were initially based on empirical correlations and the search for adimensional groups for the calculation of liquid holdup and friction factors for pressure evaluations. Later the analysis of gas-liquid interactions turned to the search for mechanistic models based on fundamental physical principles. The initial development of this topic occurred in the 1980s and 1990s. The seminal study titled “A Model for Predicting Flow Regime Transitions in Horizontal and near Horizontal Gas-Liquid Flow” was published by Taitel and Dukler in 1976. The flow types are represented by diagrams showing the gas and liquid flow rates using superficial velocities of the liquid USL and vapor USG. These maps, widely reproduced in textbooks and design manuals, are often considered cornerstones in the two-phase flow subject but have never been discussed. The results obtained in developing a mathematical model for the dynamic compositional simulation of two-phase flows, allowed the author to highlight the lack of thermodynamic bases and other approximations in calculating classical two-phase flow maps. They represent reality in a very approximate way, especially when used by chemical engineers to design two-phase transport of multicomponent mixtures. The failure to consider the vapor-liquid equilibrium in the cases of oil and gas transport is perhaps the greatest error, probably generated by the initial consideration of air-water systems only. The frequent reproduction of these flow maps in textbooks and design manuals is also a problem in the correct teaching of two-phase flow topics. The article highlights the inconsistencies introduced in the generation of two-phase flow maps presented by Taitel and Dukler in their historical study. This analysis is based on a rigorous 1D fluid dynamic simulation implemented by the author.